Decolonizing Tacit Knowledge of The Bugis Traditional House through Ethnomathematics - Yusran, Yusfan Adeputera; Utami, Sri; Fadhilah, Siti Mar atul; Sir, Mohammad Mochsen; Prijotomo, Josef (University of Merdeka Malang, 2022)
This study aims to reveal the logical factors behind the cultural values of traditional house. Through an ethnomathematical study approach, this study reconstructs various patterns of Bugis house forms using photo documentation belonging to the KITLV institution published around 1880-1953. The Bugis vernacular house forms is often described as the embodiment of the basic knowledge of non-physical (intangible) in the form of culture, belief, and the principles of community life. However, when viewed from the building process, rules, and sizes, to the development of its form and typology, a Bugis house cannot be seen as a mere embodiment of the cosmological concept, but also an embodiment of form that implements scientific knowledge. This is indicated by the various patterns of Bugis' traditional houses formed from an ethnomodelling point of view as a result of humans knowledge to the context and the environment in which they inhabit.